Efficient analysis of pharmaceutical drug substances and products using a solid-state NMR CryoProbe. Issue 4 (26th January 2023) - Du, Yong; Struppe, Jochem; Perrone, Barbara; Hassan, Alia; Codina, Anna; Su, Yongchao
Abstract : Enabling efficient pharmaceutical analysis of drug substances and products using a sensitivity enhanced magic angle spinning CryoProbe. Abstract : Solid-state nuclear magnetic resonance (ssNMR) is a high-resolution and versatile spectroscopic tool for characterizing pharmaceutical solids. However, the inherent low sensitivity of NMR remains a significant challenge in the analysis of natural abundance drug substances and products. Here, we report, for the first time, the application of a CPMAS CryoProbe™ to improve the sensitivity of 13 C and 15 N detection by approximately 5 to 6 times for solid-state analysis of a commercial pharmaceutical drug posaconazole (POSA). The sensitivity enhancement enables two-dimensional (2D) 13 C– 13 C and 1 H– 15 N correlation experiments, which are otherwise time-prohibitive using regular MAS probes, for resonance assignment and structural elucidation. These polarization transfer and correlation experiments reveal drug–drug and drug–polymer interactions in amorphous POSA and its amorphous solid dispersion formulation. Our results demonstrated that the CPMAS CryoProbe™ can be widely applied for routine pharmaceutical analysis and advanced structural investigations with significantly enhanced efficiency and throughput.